Clinical profile and outcomes in octogenarians with atrial fibrillation: A community-based study in a specific European health care area. (15th September 2017) - Rodríguez-Mañero, Moisés; López-Pardo, Estrella; Cordero, Alberto; Kredieh, Omar; Pereira-Vazquez, María; Martínez-Sande, Jose-Luis; Martínez-Gomez, Alvaro; Peña-Gil, Carlos; Novo-Platas, José; García-Seara, Javier; Mazón, Pilar; Laje, Ricardo; et al.
Abstract: Background: Age increases risk of stroke and bleeding. Clinical trial data have had relatively low proportions of elderly subjects. We sought to study a Spanish population of octogenarians with atrial fibrillation (AF) by combining different sources of electronic clinical records from an area where all medical centres utilized electronic health record systems. Methods: Data was derived from the Galician Healthcare Service information system. Results: From 383, 000 subjects, AF was coded in 7990 (2.08%), 3640 (45.6%) of whom were ≥ 80 and 4350 (54.4%) < 80. All CHA2DS2-VASc's components were more prevalent in the elderly except for diabetes. Of those ≥ 80, 2178 (59.8%) were women. Mean CHA 2 DS 2 -VASc was 4.2 ± 1.1 . Distribution of CHA 2 DS 2 -VASc components varied between genders. 2600 (71.4%) were on oral anticoagulant (OA). During a median follow up of 696 days (124.23), all-cause mortality was higher in ≥ 80 (1011/3640 (27.8%) vs 350/4350 (8.05%) ( p  < 0.001). There were differences in rate of thromboembolic (TE) and haemorrhagic events (2.3% vs 0.9%, p  < 0.01 and 2.5% vs 1.7%, p  = 0.01 respectively). In octogenarian, differences between genders were observed with regard to TE, but not in haemorrhagic or all-cause mortality rates. Age, heart failure, non-valvular AF, dementia, and OA were independent predictors of all-cause mortality. In regard to TE, female gender, hypertension, previous TE and OA were independent predictive factors. Conclusions: Octogenarians with AF had very different characteristics and outcomes from their younger counterparts. These results also provide reassurance about the effectiveness of OA in preventing TE events and maintaining a reasonable haemorrhagic event rate in the extremely elderly.